Dopamine promotes Klebsiella quasivariicola proliferation and inflammatory response in the presence of macrophages - Li, Xiang; Cheng, Lin; Liu, Xueyang; Wang, Xiaoli; Li, Rui; Fan, Shao; Yan, Qiulong; Ma, Tonghui; Ma, Yufang; Kang, Jian (Frontiers in Cellular and Infection Microbiology, 2024)
Background Dopamine, a frequently used therapeutic agent for critically ill patients, has been shown to be implicated in clinical infections recently, however, the precise mechanisms underlying this association remain elusive. Klebsiella quasivariicola, a novel strain belonging to the Klebsiella species, exhibits potential pathogenic attributes. The impact of dopamine on K. quasivariicola infection has aroused our interest. Objective Considering the contribution of host immune factors during infection, this study aimed to investigate the intricate interactions between K. quasivariicola, dopamine, and macrophages were explored. Methods RAW264.7 cells and C57/BL6 mice were infected with K. quasivariicola, and the bacterial growth within macrophage, the production of inflammatory cytokines and the pathological changes in mice lungs were detected, in the absence or presence of dopamine. Results Dopamine inhibited the growth of K. quasivariicola in the medium, but promoted bacterial growth when co-cultured with macrophages. The expression of proinflammatory cytokines increased in RAW 264.7 cells infected with K. quasivariicola, and a significant rise was observed upon the addition of dopamine. The infection of K. quasivariicola in mice induced an inflammatory response and lung injury, which were exacerbated by the administration of dopamine. Conclusions Our findings suggest that dopamine may be one of the potential risk factors associated with K. quasivariicola infection. This empirical insight provides solid references for clinical precision medicine. Furthermore, an in vitro model of microbes-drugs-host immune cells for inhibitor screening was proposed to more accurately replicate the complex in vivo environment. This fundamental work had contributed to the present understanding of the crosstalk between pathogen, dopamine and host immune cells.